The Cross Entropy Method and Its Applications - Hamad, Sarwar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
The Cross Entropy (CE) method which was initiated and developed by Reuven Rubinstein has been applied to combinatorial optimization problems with promising results. The CE method is actually a generic approach for solving combinatorial optimization. The CE method has been applied successfully to well known optimization problems such as traveling salesman, quadratic assignment problem, and the maximal cuts. In this study, the solution methodology of Traveling Salesman Problem (TSP) for different CE parameters are considered and tested. Keywords: Travelling Salesman Problem, Genetic Algorithm, CE parameter

ÖZ:Reuven Rubinstein tarafından geliştirilen Çapraz Entropi (CE) yöntemi umut verici sonuçlar ile kombinatoryel optimizasyon problemlerine uygulanmıştır. Çapraz-Entropi (CE) yöntemi CE gibi yolculuk satıcısı, kuadratik atama problemi ve maksimal kesimler olarak optimizasyon problemleri başarıyla uygulanmış olan bir kombinasyon optimizasyonu için genel bir yaklaşımdır. Bu çalışmada, farklı CE parametreleri için Satıcı Problemi (TSP) çözüm yöntemi olarak uygulandi ve testedildi. Anahtar Kelimeler: Gezgin Satıcı Problemi, Genetik Algoritma
Master of Science in Mathematics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2015. Supervisor: Assist. Prof. Dr. Arif Akkeleş.
Keywords: Mathematics; Cross-entropy method; Travelling Salesman Problem, Genetic Algorithm, CE parameter